The man who sold the world - Nirvana; Litt, Scott; Geffen Records (United States : Geffen Records, 1994)
Contains the single track taken from the DGC album MTV Unplugged in New York.
CD 1 : The Man Who Sold The World / (3:48).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Heavy metal (Music).; Rock music